RELIGIOUS SYMBOLISM IN INDONESIA - Muhammad Edy Susilo; Arif Wibawa (The Indonesian Journal of Communication Studies, 2014)
There is a very interesting phenomenon in the religious in this country. On the surface, there was tremendous excitement in religious expression. In the past two decades, moslem women wearing the hijab is still something "strange", but  now is a familiar sight. Muslim fashion industry has a turnover of billions of rupiahs. Pengajian (lectures about Islam) held in the villages to the five-star hotels. Ustadz (man who teach about Islam) and ustadzah (women who teach about Islam) has popularity like the celebrities. This is possible because on national television to accommodate them in an activity that is nuanced symbiotic mutualism. In addition to the Hajj, Umrah service is also increasingly in demand by Moslims. Umrah pilgrims worship it, every year, it exceeds the number of Hajj pilgrims. But all the  phenomenon on the surface has a paradox in what became a reality in society.  There are still significant poverty rates,  crime or sex industry. A simple analysis of the corruptor show that most of them is a figure of "religious". People prefer religious symbols because it is more easily identified by others. There is an understanding that the use of symbols that make them more comfortable and "in-group". This is  happen because a lot of media corrupt the meaning of religiosity. Media teach that religious is everything tangible: apparel, home accessories or ornaments. Likewise, that religion is a beautiful verbalisme to say. Media is also a source of reference that people can become fragmented figures: people can join Musabaqah Tilawatil Quran while becoming a  dangdut singer, Moslem women wears veil when pengajian but they are wear sexy cloth when clubbing. Understanding of society is increasingly confirmed by some ustadz who would collaborate with the television industry in build the symbolic form of Islam. “The real Ulama” (moslem scholars or religious leader) with ascetic lifestyle, enlightening the society and do not be tempted by the power increasingly hard to find. Comprehensive understanding of  religiosity became very absolutely necessary. Moslems need to be aware that the use of religious symbols should be actualized in everyday life.